2012
DOI: 10.1128/mbio.00036-12
|View full text |Cite
|
Sign up to set email alerts
|

The Black Queen Hypothesis: Evolution of Dependencies through Adaptive Gene Loss

Abstract: ABSTRACTReductive genomic evolution, driven by genetic drift, is common in endosymbiotic bacteria. Genome reduction is less common in free-living organisms, but it has occurred in the numerically dominant open-ocean bacterioplanktonProchlorococcusand “CandidatusPelagibacter,” and in these cases the reduction appears to be driven by natural selection rather than drift. Gene loss in free-living organisms may leave them depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
945
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 997 publications
(1,037 citation statements)
references
References 53 publications
40
945
0
2
Order By: Relevance
“…In addition, we also observed a significant increase in the abundance of catalase-peroxidase transcripts (Table 4). This is consistent with the 'Black Queen' hypothesis (Morris et al, 2012), which posits that the evolutionary loss of the catalase gene in Prochlorococcus was facilitated by the ability of heterotrophs to provide this 'leaky' function. Although it is unclear which, if any, of these heterotroph transcriptomic responses were specific to co-culture with Prochlorococcus as opposed to changes owing to stresses, growth or simply changes in the nutrient environment, these results support the hypothesis that the chemical conversation in the co-culture was two-sided.…”
Section: Regulation Of Transcriptional Responses To Co-culturesupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, we also observed a significant increase in the abundance of catalase-peroxidase transcripts (Table 4). This is consistent with the 'Black Queen' hypothesis (Morris et al, 2012), which posits that the evolutionary loss of the catalase gene in Prochlorococcus was facilitated by the ability of heterotrophs to provide this 'leaky' function. Although it is unclear which, if any, of these heterotroph transcriptomic responses were specific to co-culture with Prochlorococcus as opposed to changes owing to stresses, growth or simply changes in the nutrient environment, these results support the hypothesis that the chemical conversation in the co-culture was two-sided.…”
Section: Regulation Of Transcriptional Responses To Co-culturesupporting
confidence: 88%
“…This phenomenon is attributable at least in part to the role of heterotrophs in reducing the levels of toxic reactive oxygen species such as hydrogen peroxide (Morris et al, 2008(Morris et al, , 2011. This is thought to compensate for the absence of catalase in the Prochlorococcus genome, indicating that interspecies interactions have clearly influenced the evolutionary selective pressures and processes acting upon this group of organisms (Morris et al, 2012). Heterotrophs in Prochlorococcus cultures in turn receive photosynthetically fixed organic carbon and other nutrients supplied by Prochlorococcus; indeed, many heterotrophs thrive in Prochlorococcus co-cultures in the absence of any added carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many of the amino acids and vitamins Ca. U copiosus appears unable to synthesize are involved in synergistic growth 47 and may be supplied by other microbes as common community goods 48 . Based on the few spartobacterial isolates that have been cultivated 11 , culture-independent studies 10,49 and the genomic data presented here, we speculate that Ca.…”
Section: Lifestyles (Supplementarymentioning
confidence: 99%
“…Several recent studies have shown that co-occurring heterotrophic bacteria can both enhance and inhibit the growth of Prochlorococcus in laboratory co-cultures (Morris et al, 2008;Sher et al, 2011). Furthermore, such interactions may have significant effects on the viability of Prochlorococcus in the oceans, for example through scavenging by heterotrophic bacteria of reactive oxygen species (ROS) produced by Prochlorococcus (Morris et al, 2011(Morris et al, , 2012. Finally, both Prochlorococcus and related Synechococcus strains have been shown to produce a wide diversity of ribosomally-synthesized peptides, which are then post-translationally modified to form lanthipeptides and microcins (Li et al, 2010;Paz-Yepes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%